Hoi toide on the Outer Banks : the story of the Ocracoke brogue - Wolfram, Walt, 1941- (University of North Carolina Press, 1997)
"Hoi toide," for those unfamiliar with the brogue, is Ocracoker for "high tide." As many visitors to the island are quick to observe, this vibrant dialect - with its unusual pronunciation, vocabulary, and syntax - is one of Ocracoke's most distinctive cultural features. In Hoi Toide on the Outer Banks, Walt Wolfram and Natalie Schilling-Estes set out to research the brogue and encourage the preservation and celebration of an important part of a community's rich heritage. Its authors trace the dialect's history and identify its unique features - even providing a glossary and quiz to augment the reader's knowledge of Ocracoke speech. In the process, they also explore some larger questions on language and the role it plays in a culture's efforts to define and maintain itself